THE IMPLEMENTATION OF THE OCCUPATIONAL HEALTH AND SAFETY MANAGEMENT SYSTEM AND THE MATURITY LEVEL OF OCCUPATIONAL HEALTH, SAFETY, AND ENVIRONMENT ON PERFORMANCE ACHIEVEMENTS WITH CULTURE TRANSFORMATION AS AN INTERVENING VARIABLE AT PT. PLN (PERSERO) UP - Edy Saputra; Kiki Farida Ferine; M. Isa Indrawan (CV. Radja Publika, 2025)
.